Managing human-elephant conflicts: the Kenyan experience - Omondi, Patrick; Bitok, Elphas; Kagiri, Joachim (Pachyderm, 2004)
This paper reviews the increasing human/elephant conflict situation in Kenya, which is largely due to the fact that elephant habitats have been 'fragmented and reduced'. The authors note: 'If the two are to co-exist, conflicts must be minimized by decreasing the costs and increasing the benefits that come to the local communities as they interact with wildlife'. Strategies used in attempts to mitigate conflict include: electric fencing and other physical barriers such as vegetation and stone walls, problem animal control, drives or attempts to force the animals to move out the area, translocation, establishment of sanctuaries.